Highlighting the Outcome of Single Stage Multilevel Soft Tissue Surgery in Patients of Cerebral Palsy with Static Contracture (s) - Manish Kanwat; Mukesh Kalra; Alok Sud; Bhavna Sharma (International Journal of Anatomy Radiology and Surgery, 2018)
Introduction: The impact of single stage multilevel soft tissue surgeries needs to be evaluated in spastic cerebral palsy children to offer a convenient treatment option for the majority of children who are lost to follow-up. Aim: Assessment of improvement in functional abilities and locomotion after single stage multilevel soft tissue surgery by using Gross Motor Functional Classification Scale (GMFCS) scores, Functional Mobility Scores (FMS) and physical examination and to study the different complications associated with this method of treatment. Materials and Methods: This was a prospective study where, a total of 20 patients (17 boys, 3 girls; mean age 7 years 3 months; range 4 to 14 years) with spastic cerebral palsy were included. Single stage multilevel soft tissue surgery was performed. Various operative procedures done were fractional lengthening of hamstring tendon, adductor tenotomy and release, lengthening of achilles tendon using white’s method, Vulpius release and posterior tibial tendon transfer. Pre and post operative physical examination was done and GMFCS scores as well as FMS scores were calculated. The patients were followed up for six months using the above mentioned parameters. Results: All patients showed an improvement of atleast one GMFCS level (p<0.001). Similar change was also observed in functional mobility scale at three and six months (p=0.001). Range of motion of all the operated joints improved postoperatively, resulting in significant improvements in posture, sitting, gait, and hygiene of the patients. Conclusion: In developing country like India single stage multilevel soft tissue surgery is proved to be a cost effective and logistic approach. For achieving satisfactory results it should be a team effort of surgeon and rehabilitation unit.